Murder & cocktails [videorecording (DVD)] - Jackson, Ron; Bernardo, Jason; Neufeld, Jessicah; O'Shaughnessey, Colleen, 1971- (Vision Films, 2024)
A financially struggling married couple starts filming themselves for a podcast when a gunshot rings out and they find their next-door neighbor is murdered. To find the killer, they invite the other residents over to probe for clues over cocktails. It gets more complicated when another body is found. No one is safe, and no one can be trusted as they try to unravel the mystery.